USM WELCOMES 60 SOUTHERN THAI STUDENTS TO UNDERGO INTENSIVE ENGLISH COURSE IN ELIC 3 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 19 July 2016 – Learning the English Language has been given a boost for the third time at Universiti Sains Malaysia (USM), with the continuation of the English and Leadership Intensive Camp 3 (ELIC 3), to be held from 17 until 22 July 2016.